Agriscience : fundamentals and applications - Burton, L. DeVere (Clifton Park, NY : Delmar Cengage Learning, 2010)
Agriscience Fundamentals and Applications, 5th edition provides a broad-spectrum overview of the agricultural industry and the industry-based sciences, including basic principles of science as they apply to plants, animals, soils and foods, for high school students.
Includes index.
Keywords: Agriculture